Determining the Factors that Influence e-Marketplace Selection from Seller’s Perspective Using a Binary Logistic Regression Model - Purwanto, Eko; Mohd, Farahwahida binti; Long, Zalizah Awang; Purnomo, Singgih (NAROTAMA UNIVERSITY, 2024)
The rapid development of information and communication technology influences changes in aspects of life in the economic sector. The application of information and communication technology supports business development. The development of the internet has become a technology that makes business activities such as marketing and sales easier. The growth of internet users in Indonesia reached 78% of the total population. E-commerce users in Indonesia reach 34.10% of all business people in Indonesia. One place to sell online is through e-marketplace. Many e-marketplaces require sellers to select e-marketplaces as a place to sell their products online. Each e-marketplace has different characteristics, so you must consider many factors when choosing an e-marketplace. In this research, it is known that two factors are formed based on factor analysis, namely the Product Quality Factor, the Service and Quality Factor, and the System Factor. In addition, the market selection model was determined using binary logistic regression analysis. The model formed in this research is the e-marketplace selection model Tokopedia, Shopee, and Lazada. Based on the results of the feasibility model using binary logistic regression, it produces an overall e-marketplace selection model with an accuracy level of 76.13%. This evaluation model can be used by sellers who want to choose a market that suits the products offered to increase profits.